The Use of YouTube in Improving Listening Skill of 9th Grade Students of SMP N 2 Labuhan Batu Utara - Nadya Bersista E. Marbun; Ruth Monika Simanjuntak; Mutiara Rajagukguk (Journal Corner of Education, Linguistics, and Literature, 2023)
This research aims to discover the use of YouTube to improve students’ listening skills. The researcher chose the qualitative method of collecting data, consisting of observation and interviews. Researchers chose SMP N 2 Labuhan Batu Utara as the location to do research with as many as 32 students as participants to collect research data. Based on research findings on observation and interviews, researchers discovered that both students and teachers got benefits by using YouTube in learning English, especially listening skills. According to the observation results, most students enjoyed the learning process. Then according to the interview results, students were more interested in following the learning process, whereas, for the teacher, YouTube was a great medium to help her teach the students. Thus, YouTube is a suitable media that can be used to teach listening to students.